1994
DOI: 10.1146/annurev.ph.56.030194.001205
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ION Channels by Protein Phosphorylation and Dephosphorylation

Abstract: Modulation of the properties of membrane ion channels is of fundamental importance for the regulation of neuronal electrical activity and of higher neural functions. Among the many potential molecular mechanisms for modulating the activity of membrane proteins such as ion channels, protein phosphorylation has been chosen by cells to play a particularly prominent part. This is not surprising given the central role of protein phosphorylation in a wide variety of cellular, metabolic, and signaling processes (26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
297
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(302 citation statements)
references
References 80 publications
5
297
0
Order By: Relevance
“…Protein phosphorylation is an important biological process that is a possible mechanism for the regulation of the activities of ion channels and a wide variety of cellular functions [34]. In addition to being regulated by various nucleotides, the activity of the K ATP channel can be further modulated by phosphorylation events induced by activated protein kinase A and protein kinase C [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphorylation is an important biological process that is a possible mechanism for the regulation of the activities of ion channels and a wide variety of cellular functions [34]. In addition to being regulated by various nucleotides, the activity of the K ATP channel can be further modulated by phosphorylation events induced by activated protein kinase A and protein kinase C [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation and dephosphorylation of speci¢c amino acid residues is often an important mechanism of ion channel regulation [14]. A consensus protein kinase C phosphorylation site is identi¢ed in hTOSS at position 158^160 in the amino acid sequence.…”
Section: Cloning and Sequence Analysis Of Htossmentioning
confidence: 99%
“…Although the long lasting nature of [Ca 2+ ] i increase by nicotine is compatible with the ®rst hypothesis, initially put forward by Manthey (1966), the second possibility accords with recent biochemical and electrophysiological observations. In fact, molecular biology studies have shown that desensitization is an intrinsic property of ligand-gated ionotropic receptors (see review by Lena & Changeux, 1993) and that is can be modulated by intracellular second messengers via phosphorylation of certain receptor subunits (Levitan, 1994). Several studies have focussed on protein kinase C (PKC) as the [Ca 2+ ] i activated e ector which modulates desensitization of nicotinic AChRs.…”
Section: Molecular Mechanisms Underlying Modulation By [Ca 2+ ] I Of mentioning
confidence: 99%